Report on Machinery for Planning - Administrative Reforms Commission (Administrative Reforms Commission, Government of India)
We dealt, in our Interim Report on the Machinery for Planning, with some aspects of the problem of reorganising the Planning Commission, namely, its set-up, the distribution of work among its Members, the role of the National Development Council and the constitution of Planning Boards in the States for the formulation of Plans and evaluation of their performance.